Outcomes of Traumatic Brain-Injured Patients With Glasgow Coma Scale < 5 and Bilateral Dilated Pupils Undergoing Decompressive Craniectomy - Tang, Zhiji; Yang, Ruijin; Zhang, Jinshi; Huang, Qianliang; Zhou, Xiaoping; Wei, Wenjin; Jiang, Qiuhua (Frontiers in Neurology, 2021)
OBJECTIVE: Decompressive craniectomy (DC) plays an important role in the treatment of patients with severe traumatic brain injury (sTBI) with mass lesions and intractably elevated intracranial hypertension (ICP). However, whether DC should be performed in patients with bilateral dilated pupils and a low Glasgow Coma Scale (GCS) score is still controversial. This retrospective study explored the clinical outcomes and risk factors for an unfavorable prognosis in sTBI patients undergoing emergency DC with bilateral dilated pupils and a GCS score less than 5. METHODS: The authors reviewed the data from patients who underwent emergency DC from January 2012 to March 2019 in a medical center in China. All data, such as patient demographics, radiological findings, clinical parameters, and preoperative laboratory variables, were extracted. Multivariate logistic regression analysis was performed to determine the factors associated with 30-day mortality and 6-month negative neurological outcome [defined as death or vegetative state (Glasgow Outcome Scale [GOS] score 1–2)]. RESULTS: A total of 94 sTBI patients with bilateral dilated pupils and a GCS score lower than 5 who underwent emergency DC were enrolled. In total, 74 patients (78.7%) died within 30 days, and 84 (89.4%) had a poor 6-month prognosis (GOS 1–2). In multivariate analysis, advanced age (OR: 7.741, CI: 2.288-26.189), prolonged preoperative activated partial thromboplastin time (aPTT) (OR: 7.263, CI: 1.323-39.890) and low GCS (OR: 6.162, CI: 1.478-25.684) were associated with a higher risk of 30-day mortality, while advanced age (OR: 8.812, CI: 1.817-42.729) was the only independent predictor of a poor 6-month prognosis in patients undergoing DC with preoperative bilateral dilated pupils and a GCS score less than 5. CONCLUSIONS: The mortality and disability rates are extremely high in severe TBI patients undergoing emergency DC with bilateral fixed pupils and a GCS score less than 5. DC is more valuable for younger patients.